Sulfatases: Critical Enzymes for Algal Polysaccharide Processing - Hettle, Andrew G.; Vickers, Chelsea J.; Boraston, Alisdair B. (Frontiers in Plant Science, 2022)
Microbial sulfatases are important biocatalysts in the marine environment where they play a key role in the catabolic biotransformation of abundant sulfated algal polysaccharides. The sulfate esters decorating algal polysaccharides, such as carrageenan, fucoidan and ulvan, can constitute up to 40% of the biopolymer dry weight. The use of this plentiful carbon and energy source by heterotrophic microbes is enabled in part by the sulfatases encoded in their genomes. Sulfatase catalysed hydrolytic removal of sulfate esters is a key reaction at various stages of the enzymatic cascade that depolymerises sulfated polysaccharides into monosaccharides that can enter energy yielding metabolic pathways. As the critical roles of sulfatases in the metabolism of sulfated polysaccharides from marine algae is increasingly revealed, the structural and functional analysis of these enzymes becomes an important component of understanding these metabolic pathways. The S1 family of formylglycine-dependent sulfatases is the largest and most functionally diverse sulfatase family that is frequently active on polysaccharides. Here, we review this important sulfatase family with emphasis on recent developments in studying the structural and functional relationship between sulfatases and their sulfated algal polysaccharide substrates. This analysis utilizes the recently proposed active site nomenclature for sulfatases. We will highlight the key role of sulfatases, not only in marine carbon cycling, but also as potential biocatalysts for the production of a variety of novel tailor made sulfated oligomers, which are useful products in, for example, pharmaceutical or cosmetic applications.